The Role of Ownership Structure on Corporate Tax Avoidance: Evidence from Manufacturing Company in Indonesia - Najihah, Naila; Winarsih, Winarsih; Mutaharoh, Mutaharoh (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
ABSTRACT This research aims to examine the influence of company ownership structure on tax avoidance. The ownership structure in this research uses three types of ownership, namely managerial ownership, institutional ownership and foreign ownership. The sample used is manufacturing companies registered on the IDX during 2021-2022. By using purposive sampling, the final data used for analysis was 176 data. The analytical tool used is SPSS with multiple linear regression analysis. The research results support all hypotheses, showing that managerial ownership, institutional ownership and foreign ownership have a negative effect on tax avoidance. The results of this research conclude that the existence of an ownership structure tends to be reluctant to be involved in tax avoidance, because it is more interested in improving the company's reputation and business continuity in the long term.